STANDARDIZATION OF SPIROMETRY: HOW TO IMPROVE THE RESULT - M. I. Chushkin; L. A. Popova; O. N. Ots; P. V. Struchkov (Туберкулез и болезни лёгких)
The majority of errors committed during spirometry results in the lower values of test results. The objective: to compare spirometry results obtained when using standard criteria of American Thoracic Society / European Respiratory Society and visual quality control. Subjects and methods. Spirometry was performed twice in 62 patients using different quality control methods. Bland – Altman method was used for statistic analysis. Results. The values of forced volume vital capacity (FVL) and forced expiratory volume during the 1st second (FEV1) were higher when using standard criteria compared to visual quality control. The mean difference in FVL made 0.40 ± 0.28 L and in FEV1 – 0.07 ± 0.21 L.Conclusion. Using the standard criteria during spirometry can significantly improve the quality of the test and prevent errors.